การศึกษามาตรฐานความปลอดภัยของผู้ใช้เส้นทางระหว่างการก่อสร้างโครงการรถไฟฟ้าทางยกระดับ - ประพฤทธิ์ สุทธมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
At the present, the growth of elevated-train construction project in Metropolitan Bangkok is increasing progressively. However, the construction area is limited while the needs of work zone and transportation are still indispensable. As aforementioned reason, road users have to encounter with high potential risk of accident in transportation inevitably. Therefore, the purposes of this research are 1) to identify the hazardous conditions for road users in highways during the elevated-train construction period, 2) to analyse the limitations of provisions in safety standards employed from the Department of Highways and 3) to develop the additional guidelines to fulfill the lack of provisions in safety standards. The research explored the hazardous conditions along the road alignment of construction. A survey and observation including interviews of road users were employed. The case studies covered the 5 routes of elevated-train construction. The 57 hazardous conditions were identified and allocated into 6 main issues, 13 sub-issues, and 27 survey topics. These hazardous conditions were then used to indicate the limitations of provision in safety standards by applying the concept of work zone safety management. The results show that 7 topics need to be added in current implementation guidelines of safety standards, 42 details of provisions also need to be added and 1 provision does not conform to the current work zone condition. In addition, the results were verified by the 5 experienced safety officers and also collected the additional preliminary guidelines to fulfill the lack of provisions in safety standards.